Small bowel obstruction due to ingested superabsorbent beads - Hao D. Pham; Lesli A. Taylor (Elsevier, 2015)
Superabsorbent water beads have found many uses as household decorative items, crafts, and other industrial uses. We report a case of ingestion of several LiquiBlock Rainbow brand superabsorbent beads by a ten month old girl leading to small bowel obstruction requiring laparotomy and removal of the beads.